Alice : from dream to dream - Macaione, Giulio; Ball, Jacqueline A. (Boom! Box, 2018)
After moving back to Cincinnati, Alice is stuck sharing a room with her brother and with her ability to share the dreams of those sleeping close to her, it makes for an uncomfortable situation. Soon Alice is depending on her friendship with Jamie to survive, not realizing there are many secrets between her family and Jamie's.